(untitled) (Veterinary Science, 2017)
The object of the present work is to determine the anabolic utilization during the fattening period in Argentine Dutch males. In order to fix the possible benefits of this practice carried out by dairy breeders, 60 castrated male calves divided into three groups were used: the Control Group, which received no treatment, the Proferm Group, treated with 36 mg Proferm" and the FEV Group, receiving 5 ml F.E.V. at the beginning of the fattening periodo The total average weight gain obtained at 200 days was used to evaluate the animals’ development. The calves treated with Proferm got an additional weight gain at 200 days post-treatment (pO,Ol); n=20, while those treated with F.E.V. obtained a non relevant weight gain (p0,05); n=20. These results show that it is advisable the use of Proferm during the fattening period since the effect of the anabolic will be reflected later in a slight shortening of the fattening process, even though the calves gain weight below their potential in variable forage demand situations. On the contrary, the use ofF.E.Y., is not recommended under the conditions ofthis essay